Corruption manifestations as a threat to national security: new challenges and problems of counteraction in the Ukrainian realities - Bortnyk, Nadiia (2021)
There are always some plagues that can destroy a society if proper measures are not manifested, one of such devastating and consequential destructive burden is that of corruption. Corruption as we all understand and characterised has been considered as a social phenomenon recognized in many instances as one of the main negative factors for Ukraine. This is especially true of high risks for the future of the state. Unfortunately, the stigma of a corrupt state for Ukraine (one that suffers from corruption at all levels of the public and private sectors) is a negative factor, first of all, its economic attractiveness. It is clear that the above-mentioned corruption background is not only an indicator of serious problems within the country, but also creates a significant obstacle to Ukraine's international image and reputation, which, in turn, impairs the quality of potential interaction with the outside world. All this allows researchers of these processes, both domestic and foreign, to call corruption one of the most dangerous threats to Ukraine, as the most serious internal problem, which is a threat to Ukraine's national security.